Virtual target point-based obstacle-avoidance method for manipulator systems in a cluttered environment. Issue 11 (1st November 2020) - Long, Zhang
Abstract : This article presents an obstacle-avoidance method for manipulator systems working in a cluttered environment. Based on the concept of the artificial potential field, a velocity potential field method is proposed, with the attractive velocity function designed in configuration space and the repulsive velocity function designed in Cartesian space. The attractive and repulsive velocities calculated by the local information together drive the manipulator to reach the target point without colliding with obstacles. To overcome the local minima problem, virtual target points are selected based on the rapidly exploring random trees method, which can consider the global information. The manipulator reaches the virtual target points one by one until the desired target is reached. The proposed method considers both global and local information and can significantly increase the probability of achieving a feasible and continuous trajectory for manipulator systems in cluttered environments. The simulation results verify the effectiveness of the proposed method.